Promoting Gender Equality through Citizenship Education in Elementary School - Febrianti, Nurul; Mahliah, Elly (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Indonesia is one of the countries that ratified the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) and the Convention on the Rights of the Child (CRC). The consequence that must be considered is that Indonesia is obliged to solve all problems and resolve gender issues and guarantee gender and guarantee children's rights, one of which is getting the right to education. Gender equality is an agenda that cannot be ruled out in education. Both in the learning process and learning as well as being the purpose of learning. Gender based education, gender sensitive education, gender responsive education or gender mainstreaming in the field of education continues to be launched. Then, promoting gender equality to students is something that should be implemented since elementary school. Promoting gender equality not only through genderbased education by inserting values and characters in students, but also can integrate into material, models, and learning strategies. Citizenship Education is a subject that is sufficiently collected in the achievement of gender equality. This is so because in citizenship education is material that intersects with genders such as human rights, democratic education, and multicultural education. If gender perspective has been introduced early in the elementary school stage by adjusting cognitive and affective development, then it is not impossible that gender equality can be realized as one of the commitments from Sustainable Development Goals (SDGs)